Modeling of Stenotic Coronary Artery and Implications of Plaque Morphology on Blood Flow - Carlos Moreno; Kiran Bhaganagar (Modelling and Simulation in Engineering)
A diseased coronary artery has been modeled to study the implications of plaque morphology on the fluid dynamics. In our previous study, we have successfully classified the coronary plaques of 42 patients who underwent intravascular ultrasound (IVUS) into four-types (Type I, Type II, Type III, and Type IV) based on the plaque morphology. In this study, we demonstrate that, for the same degree of stenosis (height of the plaques), hemodynamics parameters are strongly dependent on the plaque shape. This study is the first one to clearly demonstrate that in addition to wall shear stress, presence of turbulence and location of transition from laminar to turbulence state are additional hemodynamics parameters to identify plaques vulnerable to rupture.